Mengungkap Kepemimpinan Lurah Kalurahan Condongcatur Kabupaten Sleman D.I. Yogyakarta - Zola, Gianfranco; Fadhlurrahman, Muhammad Dzaky; Ardaneswhari, Najla Indira (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2024)
The village is the smallest government unit in Indonesia which has the authority to manage its government for the welfare of the community as part of the right to autonomy. Villages are also the focus of national development, because the success of national development is seen from the management of village development so that it requires effective leadership to carry out its programs. One example of good village leadership is the Condongcatur Village Head, who has served two terms and brought real progress to the Condongcatur Village. This research aims to reveal the background and leadership style of the Condongcatur Village Head, the challenges he faces, the application of leadership in decision making, changes that have been made during his tenure, as well as hopes for the future of the Condongcatur Village Head. The method used is descriptive qualitative with data obtained through interviews with the Head of Condongcatur Village and studies of related literature. The research results show that the Condongcatur Village Head combines talent, skills and education in his leadership based on contingency theory. The leadership type is democratic and the leadership style is transactional while still providing an example. The challenges it faces are internal and external. In making decisions, the Condongcatur Village Head uses a team-centered model. Apart from that, he hopes to improve community services in order to achieve better prosperity.